2014
DOI: 10.3892/mmr.2014.2196
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the HMOX1 gene by the transcription factor AP-2δ with unique DNA binding site

Abstract: Abstract. AP-2 transcription factors are important sequence-specific DNA-binding regulators that are expressed in the neural crest and other tissues during mammalian development. The human AP-2 family of transcription factors consists of five members, AP-2α, -β, -γ, -δ and -ε, which have an important role in the regulation of gene expression during development and in the differentiation of multiple organs and tissues. The present study aimed to investigate the mechanism by which AP-2δ mediates heme oxygenase-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…We next identified putative TFBS associated with the differentially methylated CpG sites using TFSEARCH v1.3 software ( http://www.cbrc.jp/research/db/TFSEARCH.html ), and found that -117CpG and -97CpG are located in the binding site for the transcription factors activator protein (AP)-2 and alcohol dehydrogenase gene regulator 1 (ADR1), respectively, while no known TFBS was predicted for the -94CpG region ( Fig 6 ). AP-2 is a sequence-specific DNA-binding protein family including AP-2α, AP-2β, AP-2γ, AP-2δ, and AP-2ε, each of which binds to a GC-rich recognition sequence present in promoter and enhancer sequences, forming a vital link between cis -regulatory DNA elements and the general transcription machinery [ 68 70 ]. Bennett et al [ 71 ] found that AP-2α expression is associated with target gene methylation and decreased expression in HNSCC cell lines, and demonstrated that AP-2α acts as a suppressor for certain “tumor suppressive” genes by targeting promoter methylation and/or deacetylation via HDAC recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…We next identified putative TFBS associated with the differentially methylated CpG sites using TFSEARCH v1.3 software ( http://www.cbrc.jp/research/db/TFSEARCH.html ), and found that -117CpG and -97CpG are located in the binding site for the transcription factors activator protein (AP)-2 and alcohol dehydrogenase gene regulator 1 (ADR1), respectively, while no known TFBS was predicted for the -94CpG region ( Fig 6 ). AP-2 is a sequence-specific DNA-binding protein family including AP-2α, AP-2β, AP-2γ, AP-2δ, and AP-2ε, each of which binds to a GC-rich recognition sequence present in promoter and enhancer sequences, forming a vital link between cis -regulatory DNA elements and the general transcription machinery [ 68 70 ]. Bennett et al [ 71 ] found that AP-2α expression is associated with target gene methylation and decreased expression in HNSCC cell lines, and demonstrated that AP-2α acts as a suppressor for certain “tumor suppressive” genes by targeting promoter methylation and/or deacetylation via HDAC recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the summary of muTarget reports ( Supplementary File S1 ) includes all significant genes which were further subjected to the gene ontology analysis (biological processes) using the built-in option. AP-2δ gene targets were collected from all available sources: databases (Harmonizome which contains, e.g., TRANScription FACtor database [TRANSFAC]); ChIP-exo experiment [ 61 ] from Gene Expression Omnibus (GSE151287: currently, to the best of our knowledge, there is only one such experiment); and literature data [ 67 , 98 , 99 , 100 , 101 ]. Collectively, 1318 target genes of AP-2δ were identified ( Supplementary File S8 ).…”
Section: Methodsmentioning
confidence: 99%
“…AP2b is a direct target of Pax3-Fox1 (24), while AP2d directly regulates HO-1 expression (25). Therefore, we checked the effect of Pax3-FoxO1 on AP2d.…”
Section: Effect Of Pax3-foxo1 Fusion Protein On Ho-1 Expressionmentioning
confidence: 99%